Curcumin-Loaded Poloxamer 407 Nanoparticles for Wound Healing Applications: Characterization and Antimicrobial Potential - Cespedes, S.; Elgegren, M.; Kim, S.; Nakamatsu, J.; Torres-Ayala, L.; Castillo, D. (Springer Science and Business Media Deutschland GmbH, 2025)
Curcumin offers a promising potential for wound healing applications due to its pharmacological properties, such as antibacterial, antioxidant, and anti-inflammatory activities. This article presents the synthesis of curcumin-loaded poloxamer nanoparticles (CurP-NPs) as a potential drug delivery system for wound healing to circumvent the limitations of curcumin’s clinical utility, such as water insolubility and poor bioavailability. Curcumin and poloxamer concentrations were optimized for CurP-NPs formulation by measuring particle size, polydispersity, and zeta potential. The morphology of CurP-NPs was studied with scanning electron microscopy (SEM). The comparative studies on the antioxidant activity of lyophilized curcumin powder and CurP-NPs were carried out by ABTS cationic radical decolorization assay. Furthermore, the qualitative study of antibacterial activity was carried out by bioautography analysis against the large positive bacteria Staphylococcus aureus. The results showed that the optimal concentration of CurP-NPs was 1.33 g/L, with the smallest size of 95.37 ± 9.2 nm and a PDI of 0.28. In addition, greater antioxidant activity was observed (54%) compared to other concentrations evaluated. Ultimately, CurP-NPs showed an inhibition zone of 1.08 mm, indicating significant antimicrobial potential.
Keywords: Curcumin; Antimicrobial; Poloxamer 407; Poloxamer; Wound healing; Pharmacology; Materials science; Nanotechnology; Chemistry; Medicine; Surgery; Composite material; https://purl.org/pe-repo/ocde/ford#3.04.01